Keyhole supraorbital eyebrow approach for fully endoscopic resection of tuberculum sellae meningioma - Zheng, Xialin; Shao, Dongqi; Li, Yu; Cai, Longjie; Xie, Shan; Sun, Zhixiang; Jiang, Zhiquan (Frontiers in Surgery, 2022)
Background: The keyhole supraorbital eyebrow approach is a technique utilized for the transcranial resection of tuberculum sellae meningioma (TSM). Surgery is the first choice for TSM treatment. In this study, the safety, feasibility, limitations, and technical requirements of a keyhole supraorbital eyebrow approach for TSM resection were summarized and analyzed. Methods: Data of 11 TSM resections through the supraorbital eyebrow approach cases (four and seven on the left and right eyebrows, respectively) were retrospectively analyzed at the Neurosurgery Department of the First Affiliated Hospital of Bengbu Medical College (Bengbu, China) from November 2019 to March 2022. Results: All 11 patients were diagnosed with meningioma (World Health Organization grade I), and the extent of gross total resection was 100%. Preoperative chief complaints were symptomatic visual dysfunction (n = 7), headache and dizziness (n = 3), and accidental discovery (n = 1). Postoperative visual function improved in 83.3% of cases (10/12 eyes), and headache and dizziness were relieved in 100% of cases (3/3 patients). Postoperative intracranial infection occurred in one case and was cured by external drainage of the lumbar cistern and anti-infection treatment. There was no occurrence of postoperative olfactory dysfunction, wound infection, eyelid ptosis, cerebrospinal fluid leakage, or death. After 3–27 months of follow-up at an outpatient clinic or by telephone, there were no reports of disease recurrence or death. Conclusion: Endoscopic TSM resection through the keyhole approach is safe, feasible, and in line with the concept of minimally invasive surgery. The endoscopic equipment and technical skills of the surgeon and surgical team are important in this technique.